The Effect Of Corporate Governance, Derivative Hedging, And Risk Governance On Company Value In Manufacturing Companies Listed On The Indonesia Stock Exchange In 2018-2022 - Kern Rahman Maulana Asnawi Putra; Mahatma Kufepaksi; Sri Hasnawati (International Journal of Economics, Business and Innovation Research, 2026)
This study aims to analyze the effect of Corporate Governance, Derivative Hedging, and Risk Governance on firm value in manufacturing companies listed on the Indonesia Stock Exchange (IDX) during the period 2018–2022. The research is based on the importance of corporate governance, hedging strategies, and risk management as factors that can influence investor perception and enhance firm value. The study population consisted of 225 manufacturing companies listed on the IDX, and through purposive sampling, 45 companies were selected as samples that met the criteria. Secondary data were obtained from annual reports and analyzed using EViews software. The results indicate that Good Corporate Governance (GCG) has a positive coefficient, but does not have a significant effect on firm value. Derivative hedging also shows a positive relationship, however it is not significant in increasing firm value. Furthermore, Risk Governance is found to have no significant effect on firm value, suggesting that the risk management practices disclosed by companies have not provided a substantial impact on enhancing firm value. These findings emphasize that the three variables have not become primary determinants in shaping the firm value of manufacturing companies listed on the IDX during the study period.